Administração de medicamentos orais à criança em unidade de acolhimento institucional: avaliação da prática de enfermagem - Chaves, Caroline Magna Pessoa (2017)
The most used medication administration route in the Institutional Reception Unit (UAI) is oral. The administration of oral medications, even though it is the simplest, requires a series of complex care, which requires the nursing team to be skilled in the technique and pharmacological properties of the drugs to be administered. The objective of this study was to evaluate the practice of nursing professionals in the preparation and administration of oral medications to children in an Institutional Reception Unit. An exploratory, descriptive, observational study of a quantitative nature, developed in two Pediatric Institutional Shelters, state, Fortaleza-CE, which have a full-time nursing team. The study population consisted of 22 nursing professionals, whose sample consisted of 12 nursing techniques that participated in the oral medication administration process and were on the work scales during the study period in the investigated units. For the number of observations, the calculation for finite population was considered, with a total of 257 observations of the oral drug administration process. To collect data, an interview was conducted with the nursing team and systematic observation of the oral administration of the drug in the child, considering five steps: reading the medical prescription (3 actions), hand hygiene (12 Actions), preparation of the material (3 actions), preparation of the medication (20 actions) and medication administration (13 actions), totaling 51 actions. The data were analyzed by descriptive statistics and Pearson's Chi-square test to verify the relationship between the execution of the actions and the observation shift, training time and experience time in the pediatrics of the observed professionals. For the performance analysis of the professionals, the performance with a cutoff point of > 70% was adopted as satisfactory. As a result of the prescriptions analyzed in the two institutions, it was verified that the three actions regarding the reading of the medical prescription were satisfactory. There was adhesion to hand hygiene in only 34.6% of the observations. Of the material preparation and medication actions, ten presented satisfactory performance of the professionals (> 70%). While 13 were unsatisfactory, the most important were: "Do not mix medications in the same plastic measuring cup" (21.7%), "Prepare liquid medications by mixing the contents by shaking the bottle before administration" (27.6%); When it was necessary to fractionate the tablet with a clean or gloved hand, only the tablets previously furrowed by the manufacturer (22.2%) were used. In the administration phase of drugs, the right nine were considered, of which five had percentages of achievement > 70%, namely: right patient (82.4%), right medication (100%), right path (100%), Right time (74.7%) and right dose (93.7%). It was concluded that there was a satisfactory performance in 30 actions (59.6%) of oral medication administration. Therefore, it is necessary to implement safe care routines for professionals to develop skills in the process of administering medications to the child in UAI.